If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(x + 2) + 4 = 5(x + 4) + 4 Reorder the terms: -3(2 + x) + 4 = 5(x + 4) + 4 (2 * -3 + x * -3) + 4 = 5(x + 4) + 4 (-6 + -3x) + 4 = 5(x + 4) + 4 Reorder the terms: -6 + 4 + -3x = 5(x + 4) + 4 Combine like terms: -6 + 4 = -2 -2 + -3x = 5(x + 4) + 4 Reorder the terms: -2 + -3x = 5(4 + x) + 4 -2 + -3x = (4 * 5 + x * 5) + 4 -2 + -3x = (20 + 5x) + 4 Reorder the terms: -2 + -3x = 20 + 4 + 5x Combine like terms: 20 + 4 = 24 -2 + -3x = 24 + 5x Solving -2 + -3x = 24 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -2 + -3x + -5x = 24 + 5x + -5x Combine like terms: -3x + -5x = -8x -2 + -8x = 24 + 5x + -5x Combine like terms: 5x + -5x = 0 -2 + -8x = 24 + 0 -2 + -8x = 24 Add '2' to each side of the equation. -2 + 2 + -8x = 24 + 2 Combine like terms: -2 + 2 = 0 0 + -8x = 24 + 2 -8x = 24 + 2 Combine like terms: 24 + 2 = 26 -8x = 26 Divide each side by '-8'. x = -3.25 Simplifying x = -3.25
| 0=n/2-2 | | 8z+8-4z=32-4z | | 6(x+1)+1=4x+2(4+x) | | 2y=8x+13 | | 4x-6(4-x)=3 | | 15+10y+y=4 | | 5(2n+4)=9(6n+9)+6 | | -x^2+110x+1300=0 | | 11-4x=-6x+15 | | 20k=18+k^2 | | 3(2x+5)=3x+18 | | 3x+20=45-2x | | -5(4t-2)+6t=5t-3 | | 2x+2.3=5.7 | | 3m^2-4m+3=0 | | 2x=10-8x | | 4x+2=4(x+9) | | 2x=12-4 | | 0.18(y-2)+0.16=0.04y-0.9 | | D=11(P-15) | | 1+w+w^2=0 | | 75=29x | | 3x^(11/13)-24=0 | | 0.50x+0.05(50)=41.5 | | 3x^11/13-24=0 | | 4x^2+4xy+y^2-9=0 | | 4.25h=38.25 | | 8x*x-7x=0 | | 2x^3-5x^2-12x+30=0 | | -x^2+110x-1300=0 | | fx=9+85 | | 5(3x-4)=7(12-x) |